(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
In a broad sense, freedom of conscience is the possibility for the citizen to have and to publicly express his conception of the world around him. Thus, if in one conception it is considered that religious freedom includes the freedom of conscience, in another conception it is considered that freedom of conscience and religious freedom are two distinct freedoms. The most widely accepted theory today is that freedom of conscience has a broad scope, including religious freedom.